Environmental and cultured cyanobacteria as sources of Aedes aegypti larvicides - Farja I. Ayala, Laura M. Becerra, Jairo Quintana, Lina M. Bayona, Freddy A Ramos, Mónica Puyana, Fredy Duque, Leonardo Castellanos (Universitas Scientiarum)
In tropical countries, the control of the mosquito Aedes aegypti is a public health priority due to its role as a vector of important viral diseases. Marine cyanobacteria are recognized as abundant sources of bioactive compounds, and they constitute a potential source of insecticides useful for controlling mosquito populations and preventing epidemic outbreaks. We collected 30 benthic cyanobacterial mats in Providencia and Rosario islands (in the Colombian Caribbean) belonging to the genera Phormidium, Symploca, Oscillatoria, Lyngbya, Pseudoanabaena, Leptolyngbya, Moorea, and Dapis. Fractions of organic extracts from the most abundant environmental samples were evaluated in three bioassays, assessing (i) larvicidal activity against A. aegypti, (ii) toxicity against the brine shrimp (Artemia salina) nauplii, and (iii) acetylcholinesterase inhibition. Non-polar fractions exhibited larvicidal activity. The polar fraction from one Dapis pleuosa extract showed larvicidal activity without being toxic against A. salina nauplii. Extracts from Moorea producens exhibited the greatest toxicity against A. aegypti larvae and A. salina nauplii. From 23 cultured cyanobacterial samples, only five grew under laboratory conditions and produced enough biomass to yield organic extracts. Of these, three extracts showed strong larvicidal activity, but only the extract from Phormidium tenue showed reduced toxicity against A. salina nauplii. We detected variation among the chemical profiles and larvicidal activity of cyanobacterial consortia depending on sites and dates of collection. Our findings suggest that despite variation in chemical profiles, extracts of marine benthic cyanobacteria can be further developed as effective control agents against insect vectors, in their larval stages. The culture of marine benthic cyanobacteria needs to be further explored to provide enough biomass leading to the identification of bioactive compounds with public health applications.